Dysnatremia in Gastrointestinal Disorders - Do, Catherine; Evans, Gretta J.; DeAguero, Joshua; Escobar, G. Patricia; Lin, Henry C.; Wagner, Brent (Frontiers in Medicine, 2022)
The primary solute of the milieu intérieur is sodium and accompanying anions. The solvent is water. The kidneys acutely regulate homeostasis in filtration, secretion, and resorption of electrolytes, non-electrolytes, and minerals while balancing water retention and clearance. The gastrointestinal absorptive and secretory functions enable food digestion and water absorption needed to sustain life. Gastrointestinal perturbations including vomiting and diarrhea can lead to significant volume and electrolyte losses, overwhelming the renal homeostatic compensatory mechanisms. Dysnatremia, potassium and acid-base disturbances can result from gastrointestinal pathophysiologic processes. Understanding the renal and gastrointestinal contributions to homeostatis are important for the clinical evaluation of perturbed volume disturbances.